Война с судьбой. Палач: [роман] / А. Новиков - Новиков Александр (Воровской закон, 2005)
Экземпляры: аб. (2008) / Инвентарный номер: 52144 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Н 73 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44